Intra-operator mobile plan switching: Evidence from linked survey and billing microdata. (August 2022) - Griffin, Míde; Lyons, Sean; Mohan, Gretta; Joseph, Merin; Domhnaill, Ciarán Mac; Evans, John
Abstract: This paper examines consumers' intra-operator mobile phone plan switching in Ireland. It models the factors associated with switching outcomes, including the direction of change in expenditure and whether those who are observed to switch plans tend to arrive at more or less optimal plans given their usage. A dataset is employed that combines survey responses from mobile consumers with the same consumers' actual usage data in the period 2017–2019; this was collected by Ireland's national regulatory authority. The cost each consumer would have incurred on every plan offered in the market based on their observed usage is estimated. Using models that allow for selection into switching, associations between switching outcomes and demographic and user characteristics are modelled. Controls are included for plan and user attributes, including demographics and proxies for user sophistication and access to alternative communication options. A substantial proportion of intra-operator switchers in the sample increase expenditures when they switch plan. While many switchers move to plans that are more optimal given their usage, a slight majority move to plans that charge a higher price premium over the best available plan (based on observables) than the consumer's previous plan did. Few observable characteristics of consumers or plans seem to be significantly associated with which switches achieve greater optimality, although fixed operator effects are large and significant. These findings add to the weight of evidence which finds that many consumers fail to arrive at the best price even after switching. Highlights: This study investigates intra-operator mobile phone plan switching in Ireland. We explore this using consumer survey data linked to administrative billing data. Regressions are estimated to explain changes in expenditure and plan optimality. Most intra-operator switchers increase their expenditures when switching plan. Many switchers appear to move to less optimal plans than where they started.